Trustworthiness and authority of scholarly information in a digital age: Results of an international questionnaire. (23rd September 2015) - Tenopir, Carol; Levine, Kenneth; Allard, Suzie; Christian, Lisa; Volentine, Rachel; Boehm, Reid; Nichols, Frances; Nicholas, David; Jamali, Hamid R.; Herman, Eti; Watkinson, Anthony
Abstract : An international survey of over 3, 600 researchers examined how trustworthiness and quality are determined for making decisions on scholarly reading, citing, and publishing and how scholars perceive changes in trust with new forms of scholarly communication. Although differences in determining trustworthiness and authority of scholarly resources exist among age groups and fields of study, traditional methods and criteria remain important across the board. Peer review is considered the most important factor for determining the quality and trustworthiness of research. Researchers continue to read abstracts, check content for sound arguments and credible data, and rely on journal rankings when deciding whether to trust scholarly resources in reading, citing, or publishing. Social media outlets and open access publications are still often not trusted, although many researchers believe that open access has positive implications for research, especially if the open access journals are peer reviewed.